Management of Worker Protection Regarding the Cancellation of the Decision of the Governor of Jakarta in Postponing the Implementation of the Minimum Wage - Haryono Edi; Rosmalily binti Salleh (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The purpose of this research is to find out the legal protection for the minimum wage deferral policy. And want to know the cancellation of the decision of the governor of Jakarta on the implementation of the minimum wage. This research method uses normative law. Methods of data collection are observation, interviews with the district court judges and prosecutors involved, documentation studies through existing archives on worker protection laws and official records, and supporting books that focus on labor protection. Decree of the Minister of Manpower and Transmigration No. Kep.231/MEN/2003 concerning Suspension of Implementation of the Minimum Wage. In the Jakarta Administrative Court decision Number 62/G/2021/Ptun.Jkt and Appeal Decision No. 10/B/2014/PT.Tun.Jkt, regarding the setting for the deferral of the minimum wage, needs to be reviewed, also regarding the deadline for the completeness of the files in submitting a deferral of the minimum wage. Agreements between employers and labor unions as a prerequisite for employers to carry out are contrary to law. Unions as legal subjects can sue Ptun. Legal settlement of the cancellation of the suspension of the minimum wage, can provide legal certainty for workers, and cause consequences in the settlement through a process at the Industrial Relations Court. Companies that have been declared void of their decision to suspend wages have not carried out their obligations to pay the minimum wage by the provisions.